Implementasi Media Roda Huruf dalam Pembelajaran Membaca Kelas I di SDN Gajah 2 Jombang: Studi Kualitatif - Indah Cahyani, Riska; Dwi Rochmania, Desty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study stems from the low initial reading competency of first-grade elementary school students. Specific obstacles found in the field include students' difficulties in vowels and consonants, obstacles in arranging letters into meaningful syllables, and low fluency in reading simple sentences. This study aims to describe in depth the implementation of the Roda Huruf media at SDN Gajah 2 Jombang. This research methodology uses a qualitative approach with a descriptive design. The focus of the research subjects involved first-grade teachers and first-grade students. To obtain comprehensive data, the researcher used participatory observation techniques and in-depth interviews. All collected data were then processed using the Miles and Huberman interactive analysis model, which includes the stages of data reduction, systematic data presentation, and drawing conclusions. The validity of the findings was ensured through a technical triangulation procedure to maintain the objectivity of the research results. The results revealed that the implementation of the Roda Huruf media was carried out through four strategic phases, namely the introduction of teaching aids, giving examples by teachers, direct practice sessions by students, and providing ongoing guidance. The impact of the use of this media was seen to be very significant; A positive transformation occurred in students' affective aspects, marked by increased enthusiasm, classroom engagement, and self-confidence. Substantial improvements were made in students' ability to recognize the alphabet, combine letter sounds into syllables, and even read fluency. The Letter Wheel media has proven to be an effective and innovative learning tool for optimizing early reading skills in elementary schools.